2021
DOI: 10.3390/foods10112712
|View full text |Cite
|
Sign up to set email alerts
|

Food Consumption Patterns in Romania during the COVID-19 Pandemic

Abstract: Food consumption behavior during the COVID-19 pandemic has changed worldwide as a consequence of the restrictions imposed by law and/or due to the fear of contamination. Although some similarities are found among countries, there are still many particularities for each nation. The present study focused on Romanian consumers and their consumption behavior related to four main food categories: fruits and vegetables, meat and meat products, bread and bakery products, and milk and milk products. Frequency of buyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…Fresh and healthy food, such as fruit and vegetables, are also recommended by the World Health Organization (WHO [29]. The EU also identifies with this within the Farm to Work strategy, which aims to ensure that people have easier access to fresh fruit and vegetables [34]. The latest study revealed an unexpected positive finding, according to which, after the outbreak of COVID-19, consumers in the European Union (EU) started buying healthy products, and 58% of Europeans consumed more fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh and healthy food, such as fruit and vegetables, are also recommended by the World Health Organization (WHO [29]. The EU also identifies with this within the Farm to Work strategy, which aims to ensure that people have easier access to fresh fruit and vegetables [34]. The latest study revealed an unexpected positive finding, according to which, after the outbreak of COVID-19, consumers in the European Union (EU) started buying healthy products, and 58% of Europeans consumed more fruit and vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Meat and bakery products emerged as being substituted by fruits and vegetables after the crisis [66]. Families cook more and buy more from local producers, and these dietary patterns might last in the years to come [67]. In Brazil, no significant change in local households during the pandemic of COVID-19 was reported [68].…”
Section: Study Implicationsmentioning
confidence: 99%
“…On the other hand, the country with the slowest evolution was Romania, starting from 4% in 2011 and reaching only 19%, compared to other European countries, which reached over 25% by 2020. In addition, in terms of the evolution of online business-to-business (B2B) sales, through the delivery of products and services from one company to another, Ireland has seen the biggest evolution over the last decade, starting at 23% in 2011 and continuing up to 39% [48,49]. In terms of the evolution of B2B online sales, Denmark is similar to Ireland, starting at 28% in 2011 and continuing to grow to 38% in 2020 (Eurostat, 2020).…”
Section: Iot Technologies In the Sales Process In Europementioning
confidence: 99%